Learning Bats Handling For Oral Swab Sampling - Azmi, Sevira Nur; Rustiati, Elly Lestari; Priyambodo, Priyambodo; Saswiyanti, Enny; Srihanto, Eko Agus; Pratiwi, Dian Neli; Susandi, Waryoko (Ann Publisher, 2025)
Background. The only flying mammals, bats, play an essential role in their natural habitat. Based on the type of food, bats can be divided into two groups: fruit-eating bats and insect-eating bats. Bats rank second-highest in species diversity, with 1,439 worldwide and 239 in Indonesia. Known as reservoirs of viruses, including coronaviruses. Aims. Bats are suspected to be related to COVID-19. Under the Research Innovation and Collaboration Program - Higher Education for Technology and Innovation Project (HETI) University of Lampung 2024-2025, and in collaboration with the Lampung Disease Investigation Centre, learning the procedures for handling bats properly so as not to physically harm bats in oral swab sampling and species recognition in Braja Harjosari, directly next to Way Kambas National Park was done. Methods. The life-trapping technique uses a mist net. Bat handling for taking oral swab was carried out using the pinch grip method, which is holding both arms of the bat backwards utilizing the thumb and middle finger with the bat positioned facing upwards. Conclusion. The bat's mouth is then blown open and a cotton swab is gently inserted into the bat's mouth. Afterwards, the bat is rested, given water drops, and released into nature. Oral swab samples from 10 individual bats: frugivorous bats, Cynopterus brachyotis (n = 8), Cynopterus horsfieldii (n = 1), and insectivorous bat, Scotophilus kuhlii (n = 1).